3D investigation of dynamic behavior and sensitivity analysis of the parameters of spherical biological particles in the first phase of AFM-based manipulations with the consideration of humidity effect. (7th January 2018) - Korayem, M.H.; Mahmoodi, Z.; Mohammadi, M.
Highlights: The 3D modeling of the manipulation of spherical biological micro/nanoparticles have been performed by considering the humidity effect. The motion modes have been derived from the constructed 3D models, and the maximum cantilever tip radius for the manipulation of a spherical bioparticle has been determined. The effective parameters have been identified by using the Sobol method. Compared to the results obtained for a dry environment, in a wet environment, the critical force for the onset of particle movement diminishes by considering the moisture effect (high humidity levels). Particle radius and adhesion coefficient are the most significant and influential parameters. Abstract: The imaging and manipulation tools being the same in an AFM has necessitated the modeling and simulation of the AFM-based manipulation processes. In earlier studies, the dynamic behavior of biological particles in the course of manipulation has been modeled and simulated two-dimensionally. Now, with the advancements made in the modeling techniques, a 3D model of the manipulation of biological particles is more accurate than its 2D counterpart. In this paper, the effect of humidity has been taken into consideration in the three-dimensional modeling of the manipulation. By employing this model, the equations for the motion modes of particles (sliding, rolling, and spinning) at the onset of movement have been derived and the critical force magnitude has been obtained. In order to reduce the potential damage to the manipulated biological particle, the maximum radius of the tip has been determined. The effective parameters in this process have been extracted by performing sensitivity analysis using the Sobol method. In comparison to the results obtained for a dry environment, the results obtained by simulating the manipulation of a yeast particle in a wet environment shows that the critical force for the onset of particle movement diminishes by considering the moisture effect (high humidity levels). The parameters influencing the magnitude of the critical force include the particle radius, particle material, surface energy of the chosen substrate, amount of preload and the contact angle. Also, the results of the performed sensitivity analysis indicate a very high influence of particle radius on the critical manipulation force and a very low impact of cantilever width on the critical force. Graphical abstract: